EVALUATION OF MERDEKA CURRICULUM IN ENGLISH SUBJECTS AT JUNIOR HIGH SCHOOL: A CASE STUDY ON WRITING SKILLS - Saifan, M. Ardyansyah; Rosalina, Utami; Asipi, Lili Sururi (NextGen Education Review Journal, 2025)
The formulation of the problem in this study is The influence of Merdeka Curriculum on students' ability to write in English language learning. The background to this study is the frequent changes in the education curriculum in Indonesia since the 1952 curriculum (Rentjana Pembelajaran Teruai) which replaced the 1947 curriculum (Rentjana Pelajaran) to the current Merdeka Curriculum in accordance with the Decree of the Minister of Education, Culture, Research and Technology (Mendikbudristek) of the Republic of Indonesia number 56 of 2022 concerning Guidelines for Curriculum Implementation in the Context of Learning Recovery, this curriculum is designed to overcome learning loss and learning gaps that occurred during the COVID-19 pandemic. The purpose of this study is to determine the factors of implementing Merdeka Curriculum in teaching English writing skills in junior high schools and to find out the perceptions of teachers and students towards Merdeka Curriculum in teaching English writing skills in junior high schools. The method used in this research is descriptive qualitative research with a case study method or approach. The theoretical foundation used is the theory of Writing Theory (Hargrove & Poteet (1984: 239). The results of this study obtained eight findings which were divided into two core findings, namely the influencing factors and perceptions of teachers and students regarding the implementation of the Merdeka curriculum at SMPN 2 Banjaran.